Midwifery Care for Pregnant Women with Late-Term Pregnancy and Oligohydramnios - Finta isti kundarti; Shintya Okta Rihandhini; Dwi estuning rahayu; ira titisari; Rahajeng sisti nur rahmawati (Health and Technology Journal (HTechJ), 2025)
Late-term pregnancy is defined as a pregnancy that has reached 41 weeks and 6 days or more, which includes the risk of oligohydramnios. Proper management of late-term pregnancy is essential through labor induction to reduce the risks of morbidity and mortality. This study aims to analyze Midwifery care for pregnant women with late-term pregnancy and oligohydramnios. This study utilized a case study methodology with a thorough midwifery care approach for one patient. Data collection involved interviews, observations, physical assessments, and documentation reviews. The data were analyzed following the midwifery process steps: assessment, diagnosis, intervention, implementation, and evaluation. The case study was conducted with Mrs. R, who showed no signs of labor. A diagnosis was made of G3P2OO3 at a gestational age of 41-42 weeks, characterized by late-term pregnancy and intrauterine live fetal oligohydramnios. The intervention involved referring the patient to the hospital for labor induction. The evaluation revealed that the cesarean section was successful, and both the mother and baby were healthy after the delivery. This case highlights the significance of early detection and sound decision-making in managing overdue pregnancies to mitigate the risks of complications for both mother and newborn.